2023
DOI: 10.1097/mpg.0000000000003806
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Symptoms Profile in Gastroparesis Compared to Other Functional and Organic Gastrointestinal Diseases

Abstract: Objectives: The primary objective was to compare the patient-reported gastrointestinal symptoms profiles of pediatric patients with gastroparesis to pediatric patients with 1 of 7 other functional gastrointestinal disorders and organic gastrointestinal diseases using the Pediatric Quality of Life Inventory (PedsQL) Gastrointestinal Symptoms Scales. Methods: The gastrointestinal symptoms profiles of 64 pediatric patients with gastroparesis who manifested abnormal gastric retention based on gastric emptying scin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…These results are concurrent with several studies worldwide and in Gulf countries showing a significant co-occurrence between GERD and IBS [9][10][11][12]. GERD and IBS affect gastrointestinal motility [9,11] and can be classified as functional dyspepsia, which causes gastrointestinal upset, but the causative factor is not fully understood [21,22]. However, a systematic review reported varied frequencies of co-occurrence between GERD and IBS, ranging between 1.7% and 74.7% [18].…”
Section: Discussionsupporting
confidence: 82%
“…These results are concurrent with several studies worldwide and in Gulf countries showing a significant co-occurrence between GERD and IBS [9][10][11][12]. GERD and IBS affect gastrointestinal motility [9,11] and can be classified as functional dyspepsia, which causes gastrointestinal upset, but the causative factor is not fully understood [21,22]. However, a systematic review reported varied frequencies of co-occurrence between GERD and IBS, ranging between 1.7% and 74.7% [18].…”
Section: Discussionsupporting
confidence: 82%